Belajar Pola Kepemimpinan Paulus dalam Kasus Onesimus Bagi Penyelesaian Perselisihan Antar Majelis di Gereja Toraja Mamasa - Daen Malewa; Djoni Juli; Joni Sius; Hetti Ratna; Dominggus Ma'dika (Departement of Mathematics Education, 2023)
Paul's profile and performance are one of the highlights of this study which is related to solving problems in the Toraja Mamasa Church. Paul was able to teach, educate, and change the attitude of someone ignorant (naughty) like Onesimus to become a faithful servant (Col. 4:9). This research aims to find solutions to problems between church assemblies with the frame and paradigm of the Paulus-Philemon-Onesimus relationship in solving problems for Philemon. This research uses a descriptive qualitative method with a literature study approach. The data is collected from selected literature that discusses Paul's leadership, and how to solve a problem in the community, especially the church. The result was that Paul's leadership should be emulated by every servant and God's servants in carrying out the mission of preaching the Gospel. Paul's leadership can interact with anyone he encounters in his life. Paul was able to lead, guide and direct the Congregation to do something good. In the application of leadership, a human resource management system is needed that supports it so that its implementation can run well to achieve goals in a company (organization). Leadership has principles, functions, and goals